Ophthalmology Residency Program Director Survey on Pass/Fail U.S. Medical Licensing Exam Step 1 Scoring - Fujihashi, Ayaka; Patel, Om U.; Yadav, Ishant; Burge, Kaitlin; Haynes, William; Zaniewski, Ryan; Wagoner, Nicholas Van; Grant, Maria B. (Journal of Academic Ophthalmology, 2023)
Background Beginning January 26, 2022, the U.S. Medical Licensing Exam (USMLE) Step 1 changed from a numerical score to pass/fail (P/F). The purpose of this study was to determine the perspective of ophthalmology program directors regarding this change in evaluating applicants.Methods After institutional review board approval, a survey was sent out to program directors of all 125 ophthalmology programs accredited by the Accreditation Council for Graduate Medical Education. Survey questions asked for program demographics, the utility of USMLE Step 1 and 2 Clinical Knowledge scores in assessing applicants, and the importance of 16 different applicant metrics before and after Step 1 becomes P/F. The metrics examined were: letters of recommendation; clerkship grades; class ranking; Alpha Omega Alpha Membership; Gold Humanism Honor Society Membership; Dean's Letter; involvement and leadership; personal statement; number of abstracts, presentations, and publications; mean number of research experiences in the specialty; Step 2 Clinical Knowledge score; volunteering; preclinical grades; away rotation in the specialty; the applicant having another graduate degree; and graduation from a top 40 National Institutes of Health-funded program. Data were analyzed using nonoverlapping 95% confidence intervals.Results The survey was completed by 50 (40%) program directors. Sixty-eight percent of respondents stated a student's ranking would be considered more after USMLE Step 1 scores become P/F, and 60% stated medical schools should share clerkship shelf exam scores with residency programs. There were no significant differences in program directors' rankings of applicant metrics following the transition to P/F Step 1.Conclusion Based on our data, program directors will likely not place a greater emphasis on Step 2 scores, despite it being the only remaining objective measure for all applicants following the switch to a P/F Step 1. Nevertheless, program directors expressed an interest in receiving other objective measures, such as shelf exam scores and class ranking, as part of the application process. Notably, we found no significant changes in the rankings of various applicant metrics before and after the transition to P/F Step 1, indicating that the metrics that were important to program directors prior to the change remain just as critical in the new era of admissions.
Keywords: ophthalmology residency; USMLE Step 1; pass/fail